PECULIARITIES OF TRANSLATING OF PHRASEOLOGICAL UNITS AND PROVERBS (Proceedings of International Educators Conference, 2023)
Translation of phraseological units and proverbs is a current topic in translatology, as they are lexical combinations whose meaning is determined by the entire expression and are characterized by emotional expressiveness and conciseness. The most important stage is defining phraseological units in the text and finding an equivalent, and context plays an important role.